MENGUJI KETAHANAN SISTEM PRESIDENSIAL INDONESIA DI TENGAH POLARISASI POLITIK YANG MENINGKAT - I Nyoman Dudy Dharmawan; Nurmansyah; Elsy A Joltuwu (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The presidential system in Indonesia is designed to ensure governmental stability through a strict separation of powers between the executive and legislative branches. However, political developments following the 2024 general elections indicate that sharp political polarization has the potential to undermine the system's effectiveness. This study aims to evaluate the resilience of Indonesia's presidential system in facing contemporary political dynamics, with a particular focus on the implications of elite polarization, legal controversies surrounding Constitutional Court rulings, the erosion of legal legitimacy and the rule of law, as well as the declining public trust in state institutions. The research employs a normative-empirical approach through literature analysis, regulatory review, and secondary data from credible news sources. The findings suggest that while Indonesia’s presidential system remains relevant for maintaining governmental stability, it remains vulnerable to distortion if the system of checks and balances is not strengthened. This study recommends the reform of the party system, the strengthening of institutional independence, and the enhancement of political education to prevent deepening polarization and to ensure the sustainability of substantive democracy in Indonesia.